“Новая литература не возникает как пистолетный выстрел в ночи”. Об институциональных границах первых советских массовых писательских объединений - Dar’ia Moskovskaia; Vagif Guseinov (eSamizdat)
The article discusses early Soviet literary institutions that took on the mission of uniting the writers’ forces: VAPP (the All-Russian Association of Proletarian Writers), whose institutional practices exhibit a pronounced sectarian nature and confrontational strategies, closely related to the early Proletkul’t, and demonstrate a distinctly ‘creative’ class-based nature; FOSP (the Federation of Soviet Writers), whose institutional nature was instrumental and artificial, this institution being “the first real example of the party’s concern for establishing basic conditions for the growth of new culture in the early years of the new regime” (Metcalf); and the Organizing Committee of the Union of Soviet Writers (SSP), which, despite sharing some similarities with FOSP, fundamentally differed from the latter through direct party leadership and funding, and gradually became a state structure – the Union of Soviet Writers. The article examines the dynamics of the Organizing Committee’s structure, marked by an increasing ‘clarification’ of who held ultimate authority. These dynamics include nationwide tense discussions among writers about funding mechanisms, continued ‘showdowns’ with enemy-colleagues, the development of the concept of socialist realism as a method for unifying writers of various social backgrounds, the “organization of total control in the literary sphere” (Frezinskii), and the complete loss (through the Charter and other practices) of institutionally formalized creative freedom for members of the Writers’ Union.